Mechanistic Advances in Hypoglycemic Effects of Natural Polysaccharides: Multi-Target Regulation of Glycometabolism and Gut Microbiota Crosstalk - Liquan Zhou; Jiani Li; Chen Ding; Yimiao Zhou; Zuowei Xiao (Molecules)
Natural polysaccharides (NPs), as a class of bioactive macromolecules with multitarget synergistic regulatory potential, exhibit significant advantages in diabetes intervention. This review systematically summarizes the core hypoglycemic mechanisms of NPs, covering structure–activity relationships, integration of the gut microbiota–metabolism–immunity axis, and regulation of key signaling pathways. Studies demonstrate that the molecular weight, branch complexity, and chemical modifications of NPs mediate their hypoglycemic activity by influencing bioavailability and target specificity. NPs improve glucose metabolism through multiple pathways: activating insulin signaling, improving insulin resistance (IR), enhancing glycogen synthesis, inhibiting gluconeogenesis, and regulating gut microbiota homeostasis. Additionally, NPs protect pancreatic β-cell function via the nuclear factor E2-related factor 2 (Nrf2)/Antioxidant Response Element (ARE) antioxidant pathway and Toll-like receptor 4 (TLR4)/nuclear factor-κB (NF-κB) anti-inflammatory pathway. Clinical application of NPs still requires overcoming challenges such as resolving complex structure–activity relationships and dynamically integrating cross-organ signaling. Future research should focus on integrating multi-omics technologies (e.g., metagenomics, metabolomics) and organoid models to decipher the cross-organ synergistic action networks of NPs, and promote their translation from basic research to clinical applications.